Exploring the common problems in learning science process skills among form four students at Kota Samarahan: A case study - Sian, Barbara (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This qualitative research by case study aims to explore form four students ' common problems, the causes and solutions to the problems in learning Science Process Skills (SPS) based on their responses in an open-ended survey questionnaire. Eight students from both science and art streams were purposively selected as informants based on certain criteria. Based on ,the findings, the problems encountered by these students in learning Science Process Skills (SPS) were more prevalent among the students than teachers. The causes to these problems were also most prevalent among the students, in addition to teachers and school laboratory facilities. Several suggestions were proposed to improve teachers, school administration and students' roles in making the learning of SPS easy and fun. It is hoped that feedbacks provided by the students would give some insight for the parties involved to do their part in making the learning of SPS relevant to students' lives. vii